Women’s presence in contemporary Italy’s environmental movements, with a case study on the Mamme No Inceneritore committee - Rachele Ledda (Genre & Histoire)
This paper aims at outlining the presence of women in contemporary Italy environmental movements, which had been hardly detectible almost until the 1970 and 1980s. It was during the Epoca Liberale that the first associations for the protection of the environment and of the Italian cultural heritage appear, an era in which women were excluded from most public activities. With the advent of Fascism, the first environmental issues arose, with women at the forefront of the protests. However, after World War II, Italian women activists focus chiefly on the conquest of civil and political rights. It is only at the end of the 1970s, during a time of major political enthusiasm, that a female figure, Laura Conti, began to stand out in the environmental milieu, by denouncing the environmental disaster of Seveso, a crucial event in the history of environmentalism and political ecology in Italy. This article analyses the long posterity of Italian ecofeminism and presents a case study of a group of women embodying the environmental justice movements in Italy, the Mamme No Inceneritore.